Pengaruh latihan range of motion (ROM) ankle terhadap pencegahan terjadinya neuropati dan angiopati pada klien diabetes melitus - Djunizar Djamaludin; Setiawati Setiawati; Rika Yulendasari (Holistik Jurnal Kesehatan, 2019)
The effect of range motion (ROM) ankle exercise on prevention of neuropathy and angiopathy in patient with diabetes mellitusBackground: Based on data from Basic Health Research (2013) conducted by the Indonesian Ministry of Health in a way to obtain the proportion of DM at the age of 15 years and over, confirmed / checked whether or not they suffer from DM or not.It was found that Lampung Province was ranked as the 8th largest DM person from 33 provinces throughout Indonesia, with DM patients with 38,923 lives and 5,560 people. One complication that needs attention is diabetes foot injury and it can cause amputation. The most common cause of diabetes foot injury is peripheral neuropathy which includes damage to sensory, autonomic and motor nerves.Purpose: The purpose of this study was to determine the effect of Range of Motion (ROM) ankle exercise on prevention of neuropathy and angiopathy on diabetes patients.Methods: A quasi experimental pre and post- test with control group study design was employed. The purposive sampling with 26 participants (13 respondents intervention group and 13 respondents control group) were recruited. The interventions groups performed ROM ankle exercise in their own respective training programs for 4 weeks, whereas no training was done in the control group. Both groups intervention and control, before and after the exercise program were measured with monofilament test for neuropathy and Venous Doppler for angiopathy. The data analysis was using t-test.Results: In the intervention group there were a significant improvements after ROM ankle exercise on prevention of neuropathy with p Value 0.000 and for angiopathy with p Value 0.000. There were significant different between intervention group and control group for neuropathy (p: .004) and angiopathy (p: .031).Conclusion: To prevent neuropathy and angiopathy on diabetes patients a home exercise program with Range of Motion (ROM) ankle could be implementedKeywords: Range of Motion; Neuropathy; Angiopathy; Diabetes MellitusPendahuluan: Berdasarkan Riskesdas tahun 2013 oleh Kemenkes RI dengan melakukan wawan cara untuk mendapatkan proporsi DM pada usia 15 tahun keatas yaitu proporsi penduduk yang terdiagnosis menderita DM dan penduduk yang belum pernah didiagnosis menderita DM. Provinsi Lampung menduduki peringkat ke – 8 penyandang DM terbesar dari 33 Provinsi diseluruh Indonesia, 38.923 jiwa dan 5.560 jiwa . Salah satu komplikasi yang harus mendapat perhatian yaitu luka kaki diabetes karena dapat mengakibarkan amputasi. Penyebab terbanyak dari luka kaki diabetes yaitu neuropati perifer yang meliputi kerusakan syaraf sensorik, otonom dan motorik.Tujuan: Diketahui pengaruh Range Of Motion (ROM) Ankle terhadap pencegahan terjadinya Neuropati dan Angiopati pada pasien Diabetes Melitus.Metode: Penelitian ini mengunakan desain quasi eksperimen pre post test dengan kelompok control dan intervensi..Sampel diambil dengan menggunakan tehnik Purposive Sampling dengan jumlah sampel yaitu 26 responden. Instrument penelitian ini  menggunakan 10 gr semmens weinstein monofilament untuk  mendeteksi  Neuropati dan  Venous Doppler  Ultrasound untuk  mendeteksi angiopati. Hasil: Menunjukkan adanya pengaruh latihan Range of Motion (ROM) Ankle terhadap pencegahan neuropati dengan p Value 0.000 dan angiopati dengan p Value 0.000. Terdapat perbedaan bermakna antara kelompok intervensi dan control untuk neuropati (p: .004) dan  angiopati  (p: .031).Simpulan: Untuk mencegah terjadinya neuropati dan angiopati pada penderita DM untuk dapat melakukan latihan Range of Motion (ROM) Ankle  dirumah